FRI0220 Allogeneic mesenchymal precursor cells (MPCS): a novel approach to treating biologic refractory rheumatoid arthritis. (15th June 2017) - Kafaja, S; Segal, KR; Skerrett, D; Itescu, S; Furst, DE
Abstract : Background: Allogeneic STRO-3 immunoselected mesenchymal precursor cells (MPCs) derived from bone marrow of healthy donors are a potent, homogeneous cell population which can be activated by pro-inflammatory cytokines to release factors which polarize pro-inflammatory monocytes and T cells to an anti-inflammatory state. This is the first in human trial to assess MPC therapy in biologic refractory RA, a disease driven by monocyte and T cell activation. Objectives: To assess the safety and tolerability and to explore the clinical efficacy of MPC therapy in RA. Methods: MSB-RA001 is a phase 1B/2A randomized, double-blind, placebo-controlled, sequential, dose-escalation trial to assess the safety and explore efficacy of a single intravenous (IV) infusion of MPCs in patients with active RA who had failed to respond to at least one biologic. Efficacy endpoints included ACR 20, 50, 70, ACR core components, HAQ and DAS28. Patients were randomized to receive one IV infusion of MPC 1 million cells/kg (n=16), 2 million cells/kg (n=16), or placebo (n=16) in 2 sequential dose cohorts. The primary study period was 12 weeks. Results: Patients in all 3 treatment groups (N=16 per group) were comparable in mean age (55 y), gender (73% women), duration of RA (14 years) and prior biologic exposures. Importantly, MPC infusions were well-tolerated with no adverse infusion reactions or serious adverse events (SAE) noted over 12 weeks. At 4 and 8 weeks, both MPC groups achieved higher ACR20 levels than placebo, with the placebo group reaching similar levels by 12 weeks. Notably, at 12 weeks both ACR50 rates (31, 27, 19%) and ACR70 rates (27, 20, 0%) were higher for the 2M/kg and 1M/kg MPC groups than placebo (Figure 1 ); p=0.04 for ACR70 in 2M/kg vs. placebo. The MPC groups showed dose-related greater improvement in pain, patient global assessment (PGA) of disease and physical function vs. placebo with greater efficacy in the 2M/kg group (Table 1 ). At 12 weeks PGA and Pain were significantly reduced in 2M/kg MPC group vs. placebo (both p=0.04). MPC treatment was associated with significantly improved health-related physical function by the HAQ. Minimal clinically important difference in HAQ defined as reduction of at least -0.22 points was achieved in 93% of 2M/kg MPC vs. 25% of placebo at 12 weeks (p=0.003). Conclusions: A single infusion of MPCs was well-tolerated in RA patients. While the efficacy results are encouraging, further assessment including dose optimization is needed. The current trial is a unique early phase trial that shows promise of a future role for MPCs as a therapeutic option in biologic-refractory RA patients, a subset of the RA population with substantial remaining medical need. Disclosure of Interest: S. Kafaja: None declared, K. Segal Employee of: Mesoblast, Inc., D. Skerrett Employee of: Mesoblast, Inc., S. Itescu Employee of: Mesoblast, Inc., D. Furst: None declared